Accuracy of laser-melted patient-specific implants in genioplasty: a three-dimensional retrospective study - Rückschloß, Thomas; Ristow, Oliver; Kühle, Reinald; Bouffleur, Frederic; Roser, Christoph; Aurin, Kerstin; Engel, Michael; Hoffmann, Jürgen; Freudlsperger, Christian (Journal of cranio-maxillofacial surgery, 2020)
Purpose - To assess the accuracy of laser-melted patient-specific implants (PSI) with regard to a preoperative virtual treatment plan for genioplasty based on a new analysis method without the use of landmarks. - Materials and methods - A retrospective evaluation of a cohort of Class II and Class III patients who had undergone virtually planned orthognathic surgery (including genioplasty) was carried out. The preoperative virtual treatment plan and the postoperative outcome were fused to calculate the translational and rotational discrepancies between the 3D planning and the actual surgical outcome. - Results - The accuracy of left/right positioning was 0.25 ± 0.28 mm (p < 0.001), that of anterior/posterior positioning was 0.70 ± 0.64 mm (p < 0.001), and that of up/down-positioning was 0.45 ± 0.38 mm (p < 0.001). The rotational discrepancies were less than 2 deg. The virtually planned and postoperative positions of the chin differed significantly from each other (p < 0.001 for all rotational and translational discrepanices). - Conclusion - The findings demonstrate that PSIs can transfer the planned virtual genioplasty into the operation theatre with small but significant deviations. However, since no conclusions can be drawn from the results regarding surgical success in terms of shaping the soft tissue profile as well as the esthetic result, no superiority of PSI over traditional plate osteosynthesis can be demonstrated.
Gesehen am 21.07.2020